Microtubule-targeting agents and their impact on cancer treatment - Čermák, Vladimír; Dostál, Vojtěch; Jelínek, Michael; Libusová, Lenka; Kovář, Jan; Rösel, Daniel; Brábek, Jan (European journal of cell biology, 2020)
Microtubule-targeting agents (MTAs) constitute a diverse group of chemical compounds that bind to microtubules and affect their properties and function. Disruption of microtubules induces various cellular responses often leading to cell cycle arrest or cell death, the most common effect of MTAs. MTAs have found a plethora of practical applications in weed control, as fungicides and antiparasitics, and particularly in cancer treatment. Here we summarize the current knowledge of MTAs, the mechanisms of action and their role in cancer treatment. We further outline the potential use of MTAs in anti-metastatic therapy based on inhibition of cancer cell migration and invasiveness. The two main problems associated with cancer therapy by MTAs are high systemic toxicity and development of resistance. Toxic side effects of MTAs can be, at least partly, eliminated by conjugation of the drugs with various carriers. Moreover, some of the novel MTAs overcome the resistance mediated by both multidrug resistance transporters as well as overexpression of specific β-tubulin types. In anti-metastatic therapy, MTAs should be combined with other drugs to target all modes of cancer cell invasion.
Keywords: mikrotubuly; Migrastatics; nádory; protinádorové látky; Microtubule-targeting agents; Antineoplastic Agents; Animals; Humans; Microtubules; lidé; Cancer therapy; zvířata; Cancer metastasis; Neoplasms